Pembuatan Membran Silika Dari Bahan Alam Untuk Pemisahan Limbah Rhodamin B - Nani Agustina; Jhon Armedi Pinem; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The membrane is a selective and semi permeable layer between two phases, namely the feed phase and the permeate phase. Membrane synthesis uses silica for the treatment of Rhodamin B waste with variations of PVA 8, 10, 12, 14 ml with an operating pressure of 2, 3, 4 bar. This research produced a porous membrane. Characteristic tests conducted include SEM, flux and reflection analysis. based on membrane flux test and reflection obtained an effective membrane performance that is on the membrane composition of PVA 14 ml with operating flux at a pressure of 2, 3, 4 bars respectively is 20.68 L / m2. Based on the characteristics of permeability, selectivity, and pore membrane statistics show that the silica membrane is an ultrafiltration membrane. Keywords: Silica, membrane, Rhodamin B waste, ultrafiltration